Giving voice to the voiceless: a mixed-methods study exploring diverse fifth-grade student leadership opportunities through an elementary program - Ray, Jennifer, Ed.D. (My University, 2025)
The study of student leadership through voice is a topic that is growing in popularity as educators and researchers learn more about its value in the educational setting. This study aims to explore a program for fifth-grade students in a rural elementary school, developed to provide a participatory voice experience, offering diverse leadership opportunities in an educational setting. Many leadership programs situated in a school setting are organized in such a way that select students represent their whole community and their voice represents the voices of their peers. This program explores an alternative in which any interested fifth-grader is offered the experience to participate in a leadership role. A mixed-methods case study was conducted to explore the actual experiences of fifth-grade students participating in a job contribution program during the 2022-2023 school year in a rural elementary school. Questionnaires, interviews, focus groups, and field observations were completed to identify if a correlation existed between this lived experience and the students’ perceived self-efficacy and their connectedness to school. Findings indicate some connection between student experiences and efficacy and suggest areas for continued research in student voice.
Keywords: Efficacy; Leadership; Student voice; Elementary program; Agency; Student autonomy